UPAYA MENINGKATKAN KUALITAS PEMBELAJARAN PENDIDIKAN AGAMA TENTANG SEJARAH PERKEMBANGAN ISLAM DI INDONESIA DENGAN PENDEKATAN PROBLEM BASED LEARNING DI KELAS XII IPS 2 SMA NEGERI 4 BUKITTINGGI - Suhana Suhana (Jurnal Akrab Juara, 2018)
This study aims to determine the improvement of Islamic learning achievement and learning outcomes on the historical subject of Islamic development in Indonesia class XII IPS 2 SMA N 4 Bukittinggi through Problem Based Learning (PBL) method. This research uses observation method, test and observation sheet. The results of the observations are then analyzed and used as material for action planning in the next cycle. Data obtained then processed, to draw conclusions. The findings of the data after the analysis showed that after the first cycle, the average score obtained by the students was 75.14. In classical value is not satisfactory, then done cycle 2, the value of students has increased with the results of all learners thoroughly with an average of 80.62. Overall learning result of Islamic Religious Education on history material of Islam development in class XII IPS 2 SMA Negeri 4 Bukittinggi have increased. The implication of the result of Class Action Research (PTK) with Problem Based Learning approach can improve the learning result of PAI in the students of class XII IPS 2 SMA Negei 4 Bukittinggi. Keywords: Learning Outcomes, Problem Based Learning Approach